Disturbance estimator and smith predictor-based active rejection of stick–slip vibrations in drill-string systems. Issue 5 (3rd April 2020) - Wu, Min; Cheng, Jun; Lu, Chengda; Chen, Luefeng; Chen, Xin; Cao, Weihua; Lai, Xuzhi
ABSTRACT: Stick–slip vibrations are widespread and hazardous phenomena in drilling practice. The objective of this paper is to develop a simple and general control strategy to minimise such vibrations together with unknown disturbances. Taking into account the transmission delay of the torsional energy from the surface to downhole, a neutral-type drill-string model is established and applied rather than a lumped-parameter model that cannot provide satisfactory modelling precision. Based on this neutral-type model, the major contribution consists of the combination of disturbance estimator and smith predictor to develop a robust vibration control scheme for drill-string systems. One conspicuous advantage of this scheme is that the effects of stick–slip vibrations and external disturbances are estimated without the need for any prior knowledge in the control input channel, and are offset correspondingly. Simulations confirm that this control scheme can achieve effective suppression of stick–slip vibrations with good tracking and disturbance rejection performance.